EXPLORING THE ROLE OF PEER LESSONS IN DEVELOPING STUDENTS’ CRITICAL THINKING SKILLS IN ECONOMICS EDUCATION - Tri Indini, Salisia; Neviyani, Neviyani; Eko Cahyono, Arie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the implementation of the Peer Lessons strategy in Economics learning and its contribution to the development of students’ critical thinking skills at SMK Raudlatul Ulum Ledokombo Jember. Previous studies have largely focused on the effects of peer-assisted learning on academic achievement, while in-depth investigations into how Peer Lessons fosters critical thinking in vocational Economics education remain limited. This study contributes a contextual understanding of the relationship between peer-based instructional practices, collaborative learning processes, and critical thinking development in Economics classrooms. The findings identified four interconnected dimensions of implementation: planning, implementation, evaluation, and critical thinking development. This study employed a qualitative descriptive approach. Data were collected through classroom observations, semi-structured interviews, and document analysis involving one Economics teacher and 32 Grade XI students who directly participated in the learning process. Data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing, while source triangulation was used to enhance the trustworthiness of the findings. The findings revealed that Peer Lessons promoted active participation, collaborative interaction, and reflective learning. Students demonstrated increased confidence in asking questions, expressing opinions, responding to peers’ arguments, and analyzing Economics-related issues. Peer-based discussions facilitated conceptual understanding through accessible explanations and meaningful knowledge exchange. The study further found that heterogeneous grouping, peer tutoring, reflective evaluation, and contextual learning activities collectively supported the development of critical thinking skills. These findings suggest that Peer Lessons serves as an effective pedagogical strategy for fostering critical thinking and active engagement in vocational Economics education.